Detection and verification of tropical cyclones and depressions over the South Pacific Ocean basin using ERA‐5 reanalysis dataset. (19th April 2021) - Yeasmin, Alea; Chand, Savin; Turville, Christopher; Sultanova, Nargiz
Abstract: Tropical cyclones (TCs) are one of the most destructive synoptic systems and can cause enormous loss of life and property damages in the South Pacific island nations. The impact of tropical depressions (TDs, i.e. weaker systems that do not develop into TCs) can also be staggering in the region in terms of heavy flooding and landslides, but a lack of complete records often hinders research involving TD impacts. A methodology has been developed here to detect TDs in the ERA‐5 reanalysis dataset (the fifth generation ECMWF atmospheric reanalysis of the global climate) using the Okubo–Weiss–Zeta parameter (OWZP) detection scheme. The new South Pacific Enhanced Archive for Tropical Cyclones dataset (SPEArTC), the Dvorak analysis of satellite‐based cloud patterns over the South Pacific Ocean basin, and a rainfall dataset for various stations and historical archives have been utilized to validate ERA5‐derived TCs and TDs for the period between 1979 and 2019. Results indicate that the OWZP method shows substantial skill in capturing the realistic climatological distribution of TDs (as well as TCs) for the South Pacific Ocean in the ERA5 reanalysis, paving a way forward for future climatological studies involving the impacts of TCs and TDs over the island nations using longer‐term reanalyses products such as the 20th‐century reanalysis dataset that extends back to the 1850s. Abstract : A methodology has been developed here to detect tropical cyclones (TCs) and tropical depressions (TDs) in ERA‐5 reanalysis dataset using the Okubo–Weiss–Zeta parameter (OWZP) detection scheme. The OWZ method shows a substantial skill in capturing the realistic climatological distribution of TCs and TDs for the South Pacific Ocean in the ERA5 reanalysis, paving a way forward for future climatological studies involving the impacts of TCs and TDs over the island nations using longer‐term reanalyses products.